2019
DOI: 10.3390/su11030756
|View full text |Cite
|
Sign up to set email alerts
|

Green Activity-Based Costing Production Planning and Scenario Analysis for the Aluminum-Alloy Wheel Industry under Industry 4.0

Abstract: The industrial revolution has grown to the fourth generation, or so-called Industry 4.0. The literature on Industry 4.0 is quite extensive and involves many different dimensions; however, production costs under Industry 4.0 have seldom been discussed. On the other hand, environmental problems are increasingly serious nowadays. Activity-Based Costing is a mature accounting method that can easily trace direct and indirect product costs, based on activities, as well as trace the carbon tax to products, which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Most of the research focuses on continuous improvements in the output by adopting smart technologies in the factory and even without knowing the emerging theory of Industry 4.0 (Devezas and Sarygulov, 2017;Gilchrist, 2016). Green manufacturing is the most contemporary research, which explores the environmental protection concept throughout the life cycle of any company (Tsai et al, 2019;Leong et al, 2019). In the initial stage of the research, it was very clear from Figure 1 and Figure 2 that the concept of green is also emerging concurrently (Bartlett and Trifilova, 2010;Tsai et al, 2011;Tsai et al, 2019) in various industries with the keywords, namely, waste, reduction, transparency, repair, emission, control, etc.…”
Section: Analysis and Interpretationmentioning
confidence: 99%
“…Most of the research focuses on continuous improvements in the output by adopting smart technologies in the factory and even without knowing the emerging theory of Industry 4.0 (Devezas and Sarygulov, 2017;Gilchrist, 2016). Green manufacturing is the most contemporary research, which explores the environmental protection concept throughout the life cycle of any company (Tsai et al, 2019;Leong et al, 2019). In the initial stage of the research, it was very clear from Figure 1 and Figure 2 that the concept of green is also emerging concurrently (Bartlett and Trifilova, 2010;Tsai et al, 2011;Tsai et al, 2019) in various industries with the keywords, namely, waste, reduction, transparency, repair, emission, control, etc.…”
Section: Analysis and Interpretationmentioning
confidence: 99%
“…After applying the exclusion criteria following the reading of titles, abstracts and keywords (which should contain the terms big data OR Industry 4.0 and quality management OR decision-making), we obtained 19 articles for a detailed reading. Of the 19 resulting articles, two were excluded following a detailed reading because they did not align with the theme of quality management in Industry 4.0 (Raut et al, 2019;Tsai et al, 2019a); this finally yielded 17 articles for classification. We also analyzed the development of the 17 selected articles.…”
Section: Summary Of Selected Studiesmentioning
confidence: 99%
“…Sherazi et al [52] presented a methodology to collect energy with a LoRaWAN (long-range wide area network) and analyzed its related costs for I4.0. Tsai et al [53] suggested an optimization model for green production planning with the ABC classification and I4.0. It is worth mentioning that for the environmental aspect, searches to improve energy efficiency by means of the IoT technology in I4.0 were stressed, where sensors will enable energy use to be monitored in real time, and this information can be analyzed and shared through all the supply chain I4.0 links.…”
Section: Taxonomymentioning
confidence: 99%